1997
DOI: 10.1152/jn.1997.77.6.2910
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Effects of Serotonin on Membrane Properties of Trigeminal Motoneurons In Vitro

Abstract: Intracellular recordings from guinea pig trigeminal motoneurons (TMNs) in brain stem slices were used to determine the underlying ionic mechanisms responsible for our previously demonstrated enhancement of TMN excitability during jaw movements by serotonin (5-HT). 5-HT (0.5-100 microM) depolarized motoneurons and increased input resistance in the majority of neurons tested. Additionally, 5-HT reduced the amplitude of the postspike medium-duration afterhyperpolarization, decreased the current threshold for main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
108
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 52 publications
18
108
1
Order By: Relevance
“…In particular, in agreement with our data on striatal cholinergic interneurons, in other neuronal populations the excitatory responses to 5-HT2C receptor activation have been reported to be mediated by the closing of K + channels (Hsiao et al, 1997;Xiang et al, 2005).…”
Section: -Ht-dependent Membrane Depolarization/inward Currentsupporting
confidence: 92%
See 2 more Smart Citations
“…In particular, in agreement with our data on striatal cholinergic interneurons, in other neuronal populations the excitatory responses to 5-HT2C receptor activation have been reported to be mediated by the closing of K + channels (Hsiao et al, 1997;Xiang et al, 2005).…”
Section: -Ht-dependent Membrane Depolarization/inward Currentsupporting
confidence: 92%
“…A closure of K leak channels was shown to mediate the 5-HTinduced depolarization in dorsal vagal neurons (Hopwood and Trapp, 2005) and to be involved in the response of trigeminal and spinal cord motoneurons to 5-HT (Hsiao et al, 1997;Kjaerulff and Kiehn, 2001). In caudal raphe and nucleus accumbens and in motoneurons of the spinal cord, 5-HT has been reported to reduce Kir conductance (North and Uchimura, 1989;Bayliss et al, 1997;Kjaerulff and Kiehn, 2001).…”
Section: -Ht-dependent Membrane Depolarization/inward Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…5-HT does not evoke rhythmic firing in guinea pig trigeminal motoneurons (Hsiao et al 1997). Thus whereas in other motor systems the actions of 5-HT on motoneurons is described as modulatory, capable of shaping an on-going rhythm but not responsible for the rhythm generation itself (Heckman et al 2004), in the vibrissa motor system, 5-HT is both necessary and sufficient for generating the whisking motor pattern and thus capable of generating rhythmic whisking.…”
Section: Discussionmentioning
confidence: 92%
“…In motoneurons, 5-HT induces multiple effects including depolarization (Larkman and Kelly, 1992;Hsiao et al, 1997;, inhibition of the medium AHP following action potentials (Berger et al, 1992;Hsiao et al, 1997;Grunnet et al, 2004), and facilitation of plateau potentials (Hounsgaard et al, 1988a;Hounsgaard and Kiehn, 1989;Bennett et al, 2001;Heckman et al, 2004). It was originally suggested that the facilitation of plateau potentials was a consequence of the inhibition of the AHP (Hounsgaard and Mintz, 1988;Schmidt and Jordan, 2000).…”
Section: Multiple Effects Of 5-htmentioning
confidence: 99%